Power of paint:: Political street art confronts the authorities - Tolonen, Jonna (Street Art & Urban Creativity, 2017)
In the context of Spain’s economic crisis, waves of protests have transformed the streets of Spanish cities into sites of place-specific spatial activism. City space has been shaped through protest, marches, squatting and street art. During Spain’s austerity years, street art has become an important part of political participation. Based on artists’ interviews and on my visual ethnographic research in the Spanish cities of Madrid (2013–2016) and Valencia (2016), this paper seeks to illuminate how political street art forms a part of social expression toward the authorities. Street art is a media through which artists can question decision-makers and challenge policies made by statesmen. The examples of political street art highlight how creative contestations become barometers of dissatisfaction and how street art confronts institutional power. Ultimately, political street art is argued in Spicca and Perdue’s (2014) term as ‘spatial citizenship’ producing more polyphonic space.